Pendidikan Islam dan Kemajuan Sains: Historisitas Pendidikan Islam yang Mencerahkan - Masduki, Masduki; Masduki (Jurnal Pendidikan Islam, 2015)
Islamic education-both as an institution and subject in public schools-currently facing the serious and complicated challenge, for example the uncertainty of dichotomiousparadigm. This uncertainty appears influenced strongly by the paradigm of thinking that tends to dualistic-confrontative. A paradigm that distinguishes the two things that seem diametrically opposed and potentially cause conflict. In Islamic education discourse, known terminology such as religious education and general education, traditional and modern education, mundane and hereafter education, and so on. So it has an impact on the discussion of the material on Islamic education that tends to ignore the matters of the mundane, such as science and technology –that ever mastered by muslims in the heyday of Islamas well as another matters that actually if we examine the Qur’an as theological foundation, Muslims talk a lot about the cosmology and universality. The new discoveries in the field of genetics as a new challenge for the Islamic education that still dwell on the issue of teachers professionalism, teaching methodology and facilities..